Synaptic and intrinsic plasticity within overlapping lateral amygdala ensembles following fear conditioning - Sehgal, Megha; Ehlers, Vanessa E.; Moyer, James R. (Frontiers in Cellular Neuroscience, 2023)
New learning results in modulation of intrinsic plasticity in the underlying brain regions. Such changes in intrinsic plasticity can influence allocation and encoding of future memories such that new memories encoded during the period of enhanced excitability are linked to the original memory. The temporal window during which the two memories interact depends upon the time course of intrinsic plasticity following new learning. Using the well-characterized lateral amygdala-dependent auditory fear conditioning as a behavioral paradigm, we investigated the time course of changes in intrinsic excitability within lateral amygdala neurons. We found transient changes in the intrinsic excitability of amygdala neurons. Neuronal excitability was increased immediately following fear conditioning and persisted for up to 4 days post-learning but was back to naïve levels 10 days following fear conditioning. We also determined the relationship between learning-induced intrinsic and synaptic plasticity. Synaptic plasticity following fear conditioning was evident for up to 24 hours but not 4 days later. Importantly, we demonstrate that the enhanced neuronal intrinsic excitability was evident in many of the same neurons that had undergone synaptic facilitation immediately following fear conditioning. Interestingly, such a correlation between synaptic and intrinsic plasticity following fear Synaptic and intrinsic plasticity in overlapping LA ensemble 2 conditioning was no longer present 24 hours post-learning. These data demonstrate that intrinsic and synaptic changes following fear conditioning are transient and co-localized to the same neurons. Since intrinsic plasticity following fear conditioning is an important determinant for the allocation and consolidation of future amygdala-dependent memories, these findings establish a time course during which fear memories may influence each other.